The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/8311535
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Correlation of Basic Fibroblast Growth Factor in Serum of Patients with Diffuse Large B‐Cell Lymphoma with Clinicopathological Efficacy and International Prognostic Index

Abstract: The correlation of basic fibroblast growth factor (bFGF) in serum of patients with diffuse large B-cell lymphoma (DLBCL) with clinicopathological efficacy and International Prognostic Index (IPI) is analyzed. 115 DLBCL patients admitted to our hospital for treatment from June 2020 to June 2021 are selected as the DLBCL patient group, 65 healthy subjects who received physical examination in our hospital during the same period are selected as the healthy control group, and the serum bFGF levels of DLBCL group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%